Metro do Porto: o fim de um percurso - Couto, Daniel Fortuna do (2011)
A dimensão e complexidade da obra do Metro do Porto, bem como o impacto para a vida da área metropolitana e da cidade, conjugadas com momento de real expansão que se verifica em relação à rede e com alguma controvérsia relacionada com opções de natureza urbanística e arquitectónica, motivam a formulação de uma reflexão sobre a realidade já construída. Procurar perceber e revelar a obra arquitectónica do Metro do Porto e o seu enquadramento na obra do autor, Eduardo Souto Moura, bem como no panorama arquitectónico português, em geral, são desafios que se colocam para um entendimento do que se poderá vir a designar por “a arquitectura do metro”. This text goes through a study of the Porto’s subway line, analyzing the work of the architect Eduardo Souto de Moura. The article is developed over a spread programmatic view, taking the composition and the morphological aspects in particular. The fact that this is large dimension design process, and it is coordinated by just one architect is also emphasized. On the other hand we took special attention relating this work on the architects general work and on the context of Porto city, it’s history and characteristics. The text explores the model tendency of this project that could be seen as a different approach to each part of the design in different places, according to the natural aspects, topography or circumstantial nature, based on the same design strategy, but that is not our conclusion.